2022
DOI: 10.1027/1864-9335/a000473
|View full text |Cite
|
Sign up to set email alerts
|

When You Are Wrong on Facebook, Just Admit It

Abstract: Abstract. Intellectually humble behavior, like admitting when you are wrong, leads to better impression formation. However, online social networks (OSNs) have changed the impression formation process. We investigated the impact of wrongness admission on impression formation during an OSN argument. In four experiments ( N = 679), participants witnessed a user engage in wrongness admission, refuse to admit, or not respond, in an argument on a Facebook wall. Participants reported their impressions of whether they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…7 In online social networks, for instance, individuals who admit they are wrong have more favorable user reputation ratings (ie, are viewed as more competent and likable) than those who refuse to do so or who fail to respond to compelling arguments contrary to the user's initial position. 13,14 Porter et al 15 demonstrated in a series of 5 studies that IH predicts learning mastery behaviors (eg, persisting in the face of setbacks, exerting effort, and seeking challenges) that have been tied to higher levels of achievement. Another study revealed that those higher in IH spent more time reading sentences that contained opinions contrary to their own related to controversial topics.…”
mentioning
confidence: 99%
“…7 In online social networks, for instance, individuals who admit they are wrong have more favorable user reputation ratings (ie, are viewed as more competent and likable) than those who refuse to do so or who fail to respond to compelling arguments contrary to the user's initial position. 13,14 Porter et al 15 demonstrated in a series of 5 studies that IH predicts learning mastery behaviors (eg, persisting in the face of setbacks, exerting effort, and seeking challenges) that have been tied to higher levels of achievement. Another study revealed that those higher in IH spent more time reading sentences that contained opinions contrary to their own related to controversial topics.…”
mentioning
confidence: 99%